A comparison of optimal peak clipping and load shifting energy storage dispatch control strategies for event-based demand response - Joseph Elio; Ryan J. Milcarek (Energy Conversion and Management: X, 2023)
Buildings, specifically large commercial buildings, are key contributors to the increasing electrical energy demand that is taxing the reliability of an ageing U.S. power grid. Through utility sponsored demand response programs and electrical energy storage systems, large buildings can simultaneously save money on their electricity bill and improve power grid reliability – with little to no change in their operations. Few studies have explored demand response benefits and appropriate control strategies for large commercial buildings. In this study, optimal peak clipping and load shifting control strategies of a Li-ion battery energy storage system are formulated and analyzed over 2 years of 15-minute interval demand data for a large commercial building in the Southwest United States. Furthermore, this analysis assesses the discounted payback period of a Li-ion battery energy storage system while considering cases with and without enrollment in the local utility’s event-based demand response program. Degradation in the Li-ion battery energy storage system’s rated power and capacity are considered throughout this analysis. Key findings in this study show that enrollment in event-based demand response can provide a reasonable (<10 years) discounted payback period of Li-ion battery energy storage systems.